Double flanged prolene intrascleral fixation of Cionni capsule tension ring - Ayman M.A Elsayed; Ahmed Samir; Ahmed M.E Alyan; Ayman Lotfy (Delta Journal of Ophthalmology, 2023)
Background Transconjunctival intrascleral fixation using double flanged prolene suture was used for scleral fixation of intraocular lenses (IOLs), Cionni capsule tension ring, and Ahmed segment. This technique carries the risk of flange exposure with subsequent hypotony and inflammation. Aim This study aimed to evaluate the efficacy of combining the Hoffman pocket with the traditional technique of Cionni ring scleral fixation in the prevention of flange exposure. Patients and methods This is a prospective study that included nine cases in which scleral fixation of the Cionni ring was indicated to treat severe zonular dialysis due to pseudo-exfoliation syndrome. The patients were followed up on the first day, after 1 week, and monthly for 6 months. During each postoperative visit, slit lamp biomicroscopy was performed to evaluate the status of the cornea, IOL centration, and position of the prolene flanges. Uncorrected visual acuity and best-corrected visual acuity were recorded. Results The mean best-corrected visual acuity improved significantly from 0.21±0.1 preoperatively to 0.76±0.24, 6 months postoperatively (P=0.0056). In all cases, the IOLs were well-centered and stable all through the postoperative follow-up period which ranged from 6 to 8 months (mean=6.9±0.66 months). No hypotony or endophthalmitis were reported. Conclusion The use of the Hoffman pocket to bury the terminal flanged ends of prolene sutures proved to be an efficient method to decrease the risk of conjunctival erosion and flange exposure.